Construction of low contracted 3D skin equivalents by genipin cross‐linking. Issue 10 (20th August 2018) - Meng, Qin; Shen, Chong
Abstract: Continuous contraction of 3D skin equivalents in construction and use restricts their applications in clinical and pharmaceutical practices. So far, no effective method has been developed to inhibit such contraction. Hence, low cytotoxic cross‐linkers, 1‐ethyl‐3‐3‐dimethylaminopropylcarbodiimide hydrochloride (EDC) and genipin, are investigated to reduce the contraction in this study. As found, both genipin and EDC at 0.2 and 0.4 mmol/L are nontoxic to collagen‐entrapped fibroblasts and upregulate the extracellular matrix expression of fibroblasts in cross‐linked collagen. Particularly, collagen cross‐linking by intermediate concentrations of genipin, specifically 0.4 mmol/L, greatly reduces the contraction of 3D skin equivalents from 87% to 28% (n = 9, P < 0.05), while the collagen after EDC cross‐linking at 0.4 mmol/L still presented severe contraction of 64% over a 21‐day follow‐up period. The inhibited contraction might relate to the increased gel stiffness and slowed collagen degradation. Moreover, the genipin cross‐linking does not impair the formation of epidermal layers and improves the epidermal‐dermal junction of skin equivalents as well. In this regard, genipin cross‐linking might facilitate the applications of 3D skin equivalents in clinical practices and pharmacology testing.